A Theatrical One-act Work Dedicated to the Solemn Day Celebrated in Schools on 12 October of this 1783 year, which Marks the Centenary of the Victory against Turks at Vienna Achieved under the Leadership of King of Poland Jan III - Vaškelienė, Asta (Senoji Lietuvos literatūra, 2014)
-